Immune checkpoint inhibitor–associated myocarditis: a systematic analysis of case reports - Wang, Caie; Zhao, Guo; Zhang, Zhen; Yang, Lukui; Liu, Shihao; Li, Guifang; Wang, Hongxia; Huang, Jiaxin; Wang, Shuhang; Li, Ning (Frontiers in Immunology, 2023)
Background: Immune checkpoint inhibitors (ICIs) therapy can be complicated by their potential cardiovascular toxicities, including myocarditis. Nowadays, no prospective trials have focused on ICI-associated myocarditis optimized management. Available evidence only come from case reports or series. A systematic case reports analysis was conducted to collect and evaluate emerging evidence of ICI-associated myocarditis to provide more information to clinicians. Methods: We performed a literature search for eligible case reports or series published between January 2018 and May 2023 using the PubMed database. Then, we extracted interesting information via table form. Finally, this study included 113 publications on 106 patients with ICI-associated myocarditis. Results: Myocarditis was found to be a highly life-threatening disease, with 53.8% of cases. Over half of cases were life-threatening (G4, 23.6%) or severe (G3, 35.8%) and required glucocorticoids. Higher rates of improvement were associated with the best response to ICI for complete response/partial response (72.7% vs. 53.9%), glucocorticoid administration (30% vs. 22%), and discontinuation of ICI (58.8% vs. 32.1%). Consequently, ICI-associated G3-G4 myocarditis should be treated with a combination of discontinuation of ICIs, high-dose glucocorticoids, other drugs, chemical drugs, plasma exchange, and life support. For moderate G1 or G2 cases, discontinuation of ICIs and regular-dose glucocorticoids should be considered. Conclusions: Once full recovery or improvement was achieved; glucocorticoids can be administered at low doses or stopped. Notably, re-challenge with ICIs appears feasible after resolution or meaningful improvement of myocarditis.